A pause for thought: exercise-induced sinus arrest causing syncope in a young male. (13th April 2011) - Whitaker, John; Wright, Matthew; O'Neill, Mark
Abstract : A 32-year-old Spanish man presented to hospital after a second episode of syncope immediately following exercise. On admission, his vitals signs were stable and he had a regular heart rate of 60 bpm. ECG and transthoracic echocardiogram were normal. He completed 15 min of a BRUCE protocol exercise test. One minute and ten seconds into recovery, he lost consciousness. His ECG demonstrated sinus arrest with pauses of up to 5 s and subsequently junctional ectopy. After 38 s, his heart returned to sinus rhythm at a rate of 140 bpm and he regained consciousness. Vasovagal syncope following exercise in the absence of structural heart disease is uncommonly reported. When cases of exercise-related syncope in patients with structurally normal hearts have been reported, the typical patient is a young male who engages in physical training. Treatment strategies in patients suffering with vasovagal asystole are necessarily empirical, and careful judgement based on the specific features of the individual cases needs to be employed.